The Role of Service Quality on The Operational Effectiveness of E-Banking Services - Vely Randyantini; Ika Puji Saputri; Bagus Nurcahyo; Renny Nur’ainy (Quantitative Economics and Management Studies, 2023)
The purpose of this study was to determine the role of service quality on operational effectiveness in e-banking. The type of data used in this study is primary data collected from the e-banking user community. Primary data in the form of written questions in the form of a questionnaire given to 150 respondents. Respondents were selected based on Non Probability Sampling. The independent variable in this study is service quality (X1), while the dependent variable in this study is the operational effectiveness of e-banking services (Y). The results of this study can be concluded that the service quality variable plays a role in the operational effectiveness of e-banking services.